Caputo-fabrizio time fractional derivative applied to visco elastic MHD fluid flow in the porous medium - Uddin, Salah; Mohamad, M.; Mohamad, M. A. H.; Sufahani, Suliadi Firdaus; Kamardan, MGhazali; Mehmood, Obaid Ullah; Wahid, Fazli; Roslan, R. (Science Publishing Corporation, 2018)
In this paper the laminar fluid flow in the axially symmetric porous cylindrical channel subjected to the magnetic field was studied. Fluid model was non-Newtonian and visco elastic. The effects of magnetic field and pressure gradient on the fluid velocity were studied by using a new trend of fractional derivative without singular kernel. The governing equations consisted of fractional partial differential equations based on the Caputo-Fabrizio new time-fractional derivatives NFDt. Velocity profiles for various fractional parameter a, Hartmann number, permeability parameter and elasticity were reported. The fluid velocity inside the cylindrical artery decreased with respect to Hartmann number, permeability parameter and elasticity. The results obtained from the fractional derivative model are significantly different from those of the ordinary model.